Scent of Darkness : A Novel - Berwin, Margot (New York Vintage Contemporaries, 2013)
Evangeline is eighteen years old when her grandmother gives her the ultimate gift, a scent she has created just for her. From the moment Eva places a drop on her neck, her entire life changes. Previously unnoticed, she becomes the object of intense desire for everyone around her. Men dance close to her; women dip their noses deep into her hair; even the cats outside her bedroom cry to be near her. Gabriel, the quiet student Eva has admired from afar, falls head-over-heels in love with her. But soon the gift begins to control Eva's life: strangers follow her around, sniffing and touching her at every turn. When Eva meets Michael, an artist who barely registers her smell, Eva wonders if he is the one person who can love her for herself. Or is her scent impossible to escape?
Keywords: Perfumes -- Interpersonal attraction